Relationship Of Supervision And Work Environment With Work Satisfaction Of Seluma Barat Camp Office Of Seluma Regency - Gustini Gustini (UNIVED Press, 2022)
The title of this research is the Relationship between Supervision and Work Environment with Employee Satisfaction of the Seluma Barat District Office of Seluma Regency. This study aims to determine the relationship of supervision with employee job satisfaction and work environment relations with job satisfaction of employees of the West Seluma District Office. This study uses the analysis method of Rank Spearman correlation with SPSS. The number of research respondents was 17 people. The results showed that there was a significant relationship between supervision and employee job satisfaction with Spearman rank correlation value of 0.750 is a strong relationship because it is in the interval 0.600 - 0.799 and the hypothesis test is known to be significant value 0.001 < 0.05 so H01 is rejected Ha1 is accepted, whereas the results of the study of the relationship of the work environment with employee job satisfaction with Spearman rank correlation value of 0.692 is a strong relationship because it is in the interval 0.600 - 0.799 and the hypothesis test is known significant value 0.002 < 0.05 H02 rejected Ha2 accepted means the work environment has a significant relationship with Job satisfaction of employees of the West Seluma Sub-District Office in Seluma District.